Examining clinical characteristics of autism and links with parent perceptions of sibling relationship quality. (February 2023) - McVey, Alana J; Liu, Quinn; Bedford, Saashi A; Zaidman-Zait, Anat; Szatmari, Peter; Smith, Isabel M; Vaillancourt, Tracy; Zwaigenbaum, Lonnie; Bennett, Teresa; Duku, Eric; Elsabbagh, Mayada; Georgiades, Stelios; et al.
Research regarding autistic children's sibling relationship quality is mixed, although some literature suggests poorer quality compared to children with other disabilities or who are neurotypical. Little is known about how the clinical characteristics of autistic children relate to parent perceptions of sibling relationship quality. We drew data from a subsample of 119 children on the autism spectrum, ages 10–11 years, from an ongoing longitudinal study. Hierarchical multiple regressions tested the extent to which children's autism symptoms, behavioral difficulties, and communication abilities related to four domains of parent-rated sibling relationship quality. We also examined communication ability as a moderator of the effect of behavioral difficulties on parent-rated sibling relationship quality. More severe autism symptoms were associated with lower levels of conflict and rivalry, whereas higher communication ability was related to more relative status/power, but also conflict. Communication ability moderated the effect of behavioral difficulties such that behavioral difficulties were more closely associated with less warmth/closeness when children had weaker communication skills; behavioral difficulties were not significantly associated with other domains of sibling relationship quality. Findings underscore the importance of considering clinical characteristics and multiple domains of relationship quality to better understand how parents view the relationships between autistic children and their siblings. Lay abstract: Sibling relationship quality is important for the well-being of children on the autism spectrum and their siblings. Little is known, however, about how varied behavior and abilities of children on the autism spectrum may be associated with parent perceptions of domains of sibling relationship quality. We drew data from a subsample of 119 children on the autism spectrum (ages 10–11 years), participating in an ongoing longitudinal study. We looked at how three clinical characteristics (autism symptoms, behavioral difficulties, and communication ability) related to four areas of parent-reported sibling relationship quality (warmth/closeness, conflict, relative status/power, and rivalry). We also examined whether the strength of the association between behavioral difficulties and parent-reported sibling relationship quality was influenced by communication ability. We found that more severe autism symptoms were associated with less conflict and rivalry, and higher communication ability was associated with more relative status/power. We also found that children on the autism spectrum with more behavioral difficulties and weaker communication ability had less warmth/closeness in their sibling relationships. Our findings highlight that it is important to consider autism symptoms, behavioral difficulties, and communication ability, as well as multiple domains of relationship quality, to better understand how parents view the relationships between autistic children and their siblings. Clinically, methods for improving sibling relationships may include teaching conflict resolution strategies to children on the autism spectrum with stronger communication abilities and their siblings, and fostering sibling connection for those with lower communication abilities.